Enhanced absorption in a graphene embedded 1D guided-mode-resonance structure without back-reflector and interferometrically written gratings - Sahoo, Pankaj Kumar (2020)
A theoretical model based on the coupled mode theory is presented to calculate the absorption in a graphene embedded 1D guided-mode-resonance (GMR) structure that does not require a back reflector. The optimized graphene-GMR structure can absorb up to 70% of the incident light which far exceeds the already reported results without using any back-metal reflector or Bragg mirror. The theoretical analysis is valid for binary gratings and pyramidal gratings which are patterned using an interference lithography system. We experimentally validate our theoretical results and analyze the influence of the geometrical parameters to achieve critical coupling for the enhanced absorption.